Budaya dan Kepercayaan : Menggali Tradisi Sesajen Dalam Bentuk Pancenan di Dusun Kedung Dowo Boyolali - Putri, Anggi Ariska; Nurhuda, Abid; Maghfuroh, Ana; Lathif, Nur Muhammad (Varied Knowledge Journal, 2025)
Java is one of the islands that is rich in values and culture, one of which is an offering that is often considered as a symbol and ritual from the community to the surrounding spirits. Among the people who still carry out and believe in it is Kedung Dowo Boyolali Hamlet, most of whose citizens are adherents of Islam, but some of them still maintain the tradition of offerings on certain occasions called pancen. And the purpose of this study is to describe the Sesajen Tradition in the form of Pancenan in Kedung Dowo Boyolali Hamlet in the perspective of culture and belief. The method used is a field study with data collection techniques using observation, interviews and documentation. Then the analysis is done interactively accompanied by a triangulation model to get valid data, and finally draw conclusions. The results showed that the tradition of offerings in the form of pancenan in the hamlet of kedung dowo boyolali is still allowed if it is only considered as cultural preservation. But if there are those who think there are other forces besides Allah SWT then the tradition is prohibited because it goes into shirk. And it is appropriate for a Muslim to slowly leave traditions and cultures that are not in line with Islamic law so that they do not take root in the next generation in the future.